Causation in evidence based medicine - Kerry, Roger (2017)
Evidence based medicine (EBM) offers an established framework for the generation, interpretation, and utilisation of information in medicine and the health sciences. Central to the practice of EBM is, I argue, the notion of causation. This thesis makes an original contribution to the philosophy of EBM through a unique identification of a causal theory in EBM, and then by demonstrating a reconceptualised theory of causation better suited to evidence based person centred care. PART 1 of this thesis demonstrates that a very specific idea of causation can be witnessed within the structure of EBM. This idea is typically Humean. Through a consideration of the structure and textual narrative of EBM, it is proposed that the framework substantiates central and canonical claims. These claims relate to the core activity of EBM being the informing of clinical decision-making through the transference of causal claims from prioritised research methods. I argue that a Humean notion of causation is problematic for the central and canonical claims, thereby presenting a paradox – EBM is structured to inform clinical decision-making about causation but is inhibited from doing so by the way this very structure conceptualises causation.